LINGUISTICALLY INTERCULTURAL PROBLEMS IN LEARNING ENGLISH AS A GLOBAL LINGUA FRANCA (EGLF) - DIEMROH IHSAN (Sriwijaya University Learning and Education International Conference, 2016)
In learning English as a Lingua Franca (ELF) of the globe, Indonesian learners ofEnglish as a Foreign Language (EFL) need great effort and seriousness to copewith certain linguistic and incultural problems. If beginning EFL learners makeerrors in making sentences using certain words, it is not surprising but it is whenthey are made by quite advanced learners. However, errors should be respectedand accepted as signs of learning as no learners create errors on purpose.Teachers should realize that errors are committed due to some factors that arebeyond learners’ awareness linguistically as well as culturally. This paper isintended to describe some linguistic and incultural errors made by advanced EFLlearners and discuss some possible causes and offer ways to help them improvetheir competence and performance in the English language. The data used in thisstudy are in forms of (a) sentences made by 30 Magister program students usingcertain words given, and (b) answers they provide based on Yes/No questions andTag-questions asked. The study reveals that to make correct sentences using certainwords and correct answers to certain questions in English EFL learners arerequired to build some linguistic, pragmatic, and intercultural comptence both inIndonesian and English.